Analisis Brand Equity terhadap Keputusan Pembelian (Studi Kasus Coffee Toffee Surabaya) - Hendro Lisa; Sitie Chairhany; Martina Napratilora; Abd Syahid; M. Ilyas (STIE Perbanas Surabaya, 2020)
This study examines and analyze the significant effect of brand equity consist; brand awareness, brand association, perceived quality and brand loyality on purchased decision. Based on the literature review, this research hypothesis states that the four elements of brand equity affect purchasing decisions. This research uses survey data from Coffee Toffee visitors in Surabaya. Data were collected by questionnaire from respondent. Hypothesis testing technique is done by using multiple regression analysis. The results of this study indicate that brand awareness has a significant positive effect on purchasing decisions, brand association has no significant positive effect on purchasing decisions, the perceived quality has a significant positive effect on purchasing decisions, and brand loyalty have a significant positive effect on purchasing decisions.